Optimasi Parameter Pemesinan dengan Proses Bubut pada Respon Kekasaran dan Kekerasan Permukaan Material S45-C Menggunakan Metode Taguchi - Grey - Fuzzy - Firman Yasa Utama; Tri Hartutuk Ningsih (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2016)
Turning is a widely used machining process in which a single-point cutting tool removes material from the surface of a rotating cylindrical work piece..Process efficiency increase significantly can be obtained by optimizing the process parameters, namely spindle rotation (n), feed rate (f) and depth of cut (a). In this research will optimize the surface roughness and hardness simultaneously using a combination of turning process parameters. The research was conducted on the material S45-C. Taguchi method is used, which is a combination of fuzzy logic and Taguchi method. Matlab software that has Matlab fuzzy toolbox aided fuzzy logic process. Design experiment using orthogonal array L9 (33) varying the three parameters which each parameters has three levels. Experiment design of L9 orthogonal array varied factor or cutting parameters such as spindle rotation (n), feed rate (f) and depth of cut (a). Since noise factors are excluded from the experimental design, the experiments were conducted with replication. Optimization was done by using grey-fuzzy Taguchi method. The results of the optimization process is a combination of parameters that result in an optimal response. Based on a combination of these parameters will be carried out confirmation test. Confirmation test was done to match the prediction results with the actual response.The results showed a combination of turning process parameters of S45-C that can generate the optimal response is spindle rotation (n)605 Rpm, feed rate (f) of 0,031 mm/minand depth of cut (a) of0,125 mm.